Observation of Ising-like critical fluctuations in frustrated Josephson junction arrays with modulated coupling energies - Affolter, J.; Tesei, M.; Pastoriza, H.; Leemann, C.; Martinoli, P. (Elsevier, 2002)
Fil: Pastoriza, H. Comisión Nacional de Energía Atómica; Argentina